Self-reported prevalence of endometriosis and its symptoms among Puerto Rican women - Flores, Idhaliz (2007)
OBJECTIVE: To determine the prevalence of endometriosis and its symptoms in a Puerto Rican cohort, and to describe the menstrual, obstetric, and clinical profiles of the women. METHODS: A self-administered questionnaire was given to 1285 Puerto Rican women. Categorical variables were compared using χ(2) analysis or Fisher exact test. RESULTS: There were 57 self-reported cases of endometriosis (48 surgically confirmed) among 1193 valid questionnaires, for a point prevalence of 4.0%. A diagnosis of endometriosis was significantly associated with dysmenorrhea, dyspareunia, and chronic pelvic pain, but not with menstrual cycle characteristics. Undiagnosed women commonly reported signs and symptoms of endometriosis. CONCLUSIONS: The estimated prevalence of endometriosis in Puerto Rico is 4.0%, comparable to what has been reported in other populations. Endometriosis symptoms were common in the population surveyed, indicating the need for increased awareness and development of public health policies leading to early diagnosis and appropriate management.